Combinatorial treatment for spinal muscular atrophy: An Editorial for 'Combined treatment with the histone deacetylase inhibitor LBH589 and a splice‐switch antisense oligonucleotide enhances SMN2 splicing and SMN expression in Spinal Muscular Atrophy cells' on page 264. Issue 2 (14th February 2020) - Poletti, Angelo; Fischbeck, Kenneth H.
Abstract: Spinal muscular atrophy (SMA) is a severe autosomal recessive motor neuron disease caused by the loss of SMN1, which encodes a protein essential for motor neuron survival. SMA patients have one or more copies of an alternate SMN gene, SMN2, which is nearly identical to SMN1 . SMN2 differs at a single nucleotide from SMN1 which results in the skipping of exon 7 in the mRNA and produces an unstable protein (SMNΔ7). Therapeutic approaches that have been undertaken include (1) replacement of SMN1 by gene delivery mediated by adeno‐associated virus serotype 9 (AAV9) (Zolgensma), (2) correction of the aberrant SMN2 splicing using an antisense oligonucleotide (ASO) or small molecule (nusinersin, risdiplam), and (3) increased expression of SMN2 mediated by histone deacetylase (HDAC) inhibitors. Two of these three approaches have given rise to successful treatments for SMA, but they are very expensive, and their long‐term safety is not well known. In addition, the ability of ASOs and viral vectors to reach their targets in the CNS with peripheral administration is limited. Small molecules may cross the brain–blood barrier when orally delivered and can be discontinued if needed to mitigate adverse effects. This Editorial highlights this study by Pagliarni et al. in which they used combined treatment of cell models of SMA with an ASO and an orally delivered HDAC inhibitor (panobinostat) to overcome the limitations of a single‐therapeutic approach. Panobinostat enhanced the expression of SMN2, increasing the amount of SMN2 mRNA available for splicing correction mediated by the ASO. In addition, panobinostat increased exon 7 retention in the SMN2 mRNA. This combinatorial treatment might allow lower or less frequent ASO doses, reducing the need for repeated intrathecal administration. The combined effects of panobinostat and nusinersen can now be tested in SMA animal models to determine whether this approach will be translatable to patients. Abstract : Spinal muscular atrophy (SMA) is a motoneuron disease caused by the loss of the gene SMN1, encoding a protein essential for motoneuron survival. Additional copies of an alternate SMN gene, SMN2, are present in the genome, but exon 7 is skipped in SMN2 mRNA producing an unstable protein (SMNΔ7). Therapeutic approaches for SMA include (1) viral‐mediated replacement of SMN1, (2) antisense oligonucleotide (ASO) or small molecule mediated correction SMN2 splicing, and (3) increased SMN2 expression induced by histone deacetylase (HDAC) inhibitors. This Editorial highlights this study by Pagliarni et al. in which they used combined treatment of cell models of SMA with an ASO and an orally delivered HDAC inhibitor (panobinostat) to overcome the limitations of a single‐therapeutic approach.